The volume of a rectangular prism is its length times width times height, or algebraically,
![V=lwh](https://tex.z-dn.net/?f=V%3Dlwh)
. You may be used to computing volume with numbers, but remember, a variable is a stand-in for a number. So you can solve this in the same way. Substitute
![l=x, w= \frac{x}{2},h= \frac{x}{3}](https://tex.z-dn.net/?f=l%3Dx%2C%20w%3D%20%5Cfrac%7Bx%7D%7B2%7D%2Ch%3D%20%5Cfrac%7Bx%7D%7B3%7D%20)
into the formula for volume. You get
![(x)( \frac{x}{2})( \frac{x}{3} )](https://tex.z-dn.net/?f=%28x%29%28%20%5Cfrac%7Bx%7D%7B2%7D%29%28%20%5Cfrac%7Bx%7D%7B3%7D%20%29)
, and you multiply these factors together. As you would with ordinary fractions, multiply the numerators and denominators across. You get
![\frac{(x)(x)(x)}{(1)(2)(3)} = \frac{x^3}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28x%29%28x%29%28x%29%7D%7B%281%29%282%29%283%29%7D%20%3D%20%20%5Cfrac%7Bx%5E3%7D%7B6%7D%20)
. It seems that the book wants you to simplify by bringing the 6 up to the denominator. Recall the rule
![x^{-n}= \frac{1}{x^n}](https://tex.z-dn.net/?f=x%5E%7B-n%7D%3D%20%5Cfrac%7B1%7D%7Bx%5En%7D%20)
, if n is non-negative. The opposite applies so that
![\frac{1}{6} = 6^{-1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B6%7D%20%3D%206%5E%7B-1%7D)
. For your final answer, you write
![6^{-1}x^3](https://tex.z-dn.net/?f=6%5E%7B-1%7Dx%5E3)
. This corresponds to
answer choice B.
To find the cost of one CD, we divide 38.04 by 4
38.04 ÷ 4 = 9.51
The answer is reasonable because it's an accurate answer.
Answer:
<em>☆</em><em><</em><em> </em><em><u>《</u></em><em><u>HOPE IT WILL HELP YOU</u></em><em>》</em><em>></em><em>☆</em>
Step-by-step explanation:
Y=1.5x+2
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>1</u></em><em><u>)</u></em></h3>
y=1.5 (1) +2
y=1.5+2
y=3.5
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>2</u></em><em><u>)</u></em></h3>
y=1.5(2)+2
y=3+2
y=5
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>3</u></em><em><u>)</u></em></h3>
y=1.5 (3)+2
y=4.5+2
y=6.5
<h3>(x=4)</h3>
y=1.5 (4)+2
y=6+2
y=8
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>5</u></em><em><u>)</u></em></h3>
y=1.5 (5)+2
y=7.5+2
y=9.5
<h2>
<em><u>please</u></em><em><u> </u></em><em><u>mark my ans as BRAIN</u></em><em><u> </u></em><em><u>LIST</u></em></h2>
I believe the answer is 104.
2/ 3 - (3 - 1) * 3 - 1 = -4
Simplify
= 2/-4
which is
= -2/4
Then simplify again
= -1/2